Predictive Load Angle and Stator Flux Control of SynRM Drives for the Full Speed Range - Hadla, Hazem Radwan (2019)
Thesis in the scope of the PhD in Electrical and Computer Engineering, specialization in Energy, presented to the Faculty of Sciences and Technology of the University of Coimbra.